Neurologic Sequelae of Tuberculous Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
A novel scoring system has been developed to predict neurologic sequelae (NS) in children with tuberculous meningitis, in a retrospective study of 20 cases treated during 1991-2001 at the University of California and Children's Hospital, San Diego, CA.